Prairie Forge : The Extraordinary Story of the Nebraska Scrap Metal Drive of World War II - Kimble, James J., 1966- (Book collections on Project MUSE., 2014)
In the wake of Pearl Harbor, President Roosevelt called for the largest arms buildup in our nation's history. A shortage of steel, however, quickly slowed the program's momentum, and arms production fell dangerously behind schedule. The country needed scrap metal. Henry Doorly, publisher of the Omaha World-Herald, had the solution. Prairie Forge tells the story of the great Nebraska scrap drive of 1942-a campaign that swept the nation and yielded five million tons of scrap metal, literally salvaging the war effort itself. James J. Kimble chro.